Combination of thermal transfer sheet and thermal transfer image receiving sheet
The combination of a thermal transfer sheet and a thermal transfer image receiving sheet, with specific layer compositions and criteria, addresses the risk of damaging print glossiness during the transfer process, achieving high glossiness and durability in the printed product.
Patent Information
- Application Number
- JP2020205201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2020-12-10
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-12-10
AI Technical Summary
The existing sublimation type thermal transfer method risks damaging the glossiness of prints when transferring the transfer layer onto a print with a glossy layer.
A combination of a thermal transfer sheet and a thermal transfer image receiving sheet is designed, where the thermal transfer sheet includes a first substrate and a transfer layer, and the thermal transfer image receiving sheet includes a second substrate, a glossy layer, and a receiving layer. The combination satisfies specific glossiness and DOI (Double Imaging) criteria to ensure high glossiness and durability of the printed product.
The proposed combination effectively produces prints with high glossiness while maintaining the durability of the printed material, ensuring that the glossiness is not compromised during the transfer process.
Smart Images

Figure 0007659739000003 
Figure 0007659739000004 
Figure 0007659739000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a combination of a thermal transfer sheet and a thermal transfer image receiving sheet. [Background technology]
[0002] Various image forming methods are known in the art. Among them, the dye-sublimation thermal transfer method is excellent in reproducibility of intermediate colors and gradations because it allows the density gradation to be freely adjusted, and it is possible to form high-quality images comparable to silver halide photography.
[0003] In the dye-sublimation thermal transfer method, a thermal transfer sheet having a coloring material layer and a thermal transfer image receiving sheet having a receiving layer are superimposed, and then the thermal transfer sheet is heated by a thermal head of the printer to transfer the sublimation dye in the coloring material layer to the receiving layer of the thermal transfer image receiving sheet, thereby forming an image and obtaining a printed matter. In addition, a transfer layer is transferred from the thermal transfer sheet onto the receiving layer of the printed matter thus produced, thereby improving the durability of the printed matter.
[0004] In recent years, a wide variety of designs are required for printed matter. For example, printed matter is required to have a high gloss. In order to obtain printed matter with a high gloss, a thermal transfer image receiving sheet having a glossy layer has been proposed (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2000-118152 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, when a transfer layer is transferred onto a print having a glossy layer, there is a risk that the glossiness of the print may be impaired.
[0007] An object of the present disclosure is to provide a combination of a thermal transfer sheet and a thermal transfer image receiving sheet that can produce a printed matter having a high gloss appearance. [Means for solving the problem]
[0008] The combination of the thermal transfer sheet and the thermal transfer image receiving sheet of the present disclosure is The thermal transfer sheet includes a first substrate and a transfer layer. The following formula (1-1) is satisfied. (20 degree gloss of thermal transfer image receiving sheet) - (20 degree gloss of thermal transfer image receiving sheet after transfer of transfer layer) ≦ 200% (1-1) Effect of the Invention
[0009] By combining the thermal transfer sheet of the present disclosure with a thermal transfer image receiving sheet, a printed matter having a high glossiness can be produced. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a combination of a thermal transfer sheet and a thermal transfer image-receiving sheet of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of a thermal transfer sheet constituting a combination of a thermal transfer sheet and a thermal transfer image receiving sheet of the present disclosure. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing one embodiment of a thermal transfer sheet constituting a combination of a thermal transfer sheet and a thermal transfer image receiving sheet of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The embodiment of the combination of the thermal transfer sheet and the thermal transfer image receiving sheet of the present disclosure will be described with reference to the drawings. Fig. 1 is a schematic cross-sectional view showing one embodiment of the combination, and Figs. 2 and 3 are schematic cross-sectional views showing one embodiment of the thermal transfer sheet.
[0012] As shown in Fig. 1, the combination of the thermal transfer sheet and the thermal transfer image receiving sheet of the present disclosure includes a thermal transfer sheet 10 and a thermal transfer image receiving sheet 20. Hereinafter, the combination of the thermal transfer sheet and the thermal transfer image receiving sheet of the present disclosure will also be simply referred to as the "combination of the present disclosure."
[0013] 1, a thermal transfer sheet 10 includes a first substrate 11 and a transfer layer 12. In one embodiment, the transfer layer 12 includes at least a release layer 13, as shown in FIG. In one embodiment, transfer layer 12 comprises a heat seal layer 14 on a release layer 13 as shown in FIG. In one embodiment, the transfer layer 12 includes an intermediate layer 15 between the release layer 13 and the heat seal layer 14, as shown in FIG. In one embodiment, as shown in FIGS. 1 to 3, the thermal transfer sheet 10 includes a back layer 16 on the surface of the first substrate 11 opposite to the surface on which the transfer layer 12 is provided. In one embodiment, the thermal transfer sheet 10 includes a color material layer (not shown) in frame sequence with the transfer layer 12. The thermal transfer sheet 10 may include a plurality of color material layers.
[0014] In one embodiment, as shown in FIG. 1, a thermal transfer image receiving sheet 20 includes a second substrate 21, a glossy layer 22, and a receiving layer . In one embodiment, the thermal transfer image receiving sheet 20 includes a primer layer (not shown) between any layers. In one embodiment, the thermal transfer image receiving sheet 20 includes a porous layer (not shown) between any layers. In one embodiment, the thermal transfer image receiving sheet 20 includes an adhesive layer (not shown) between any layers.
[0015] The combination of the present disclosure satisfies the following formula (1-1). (20 degree gloss of thermal transfer image receiving sheet) - (20 degree gloss of thermal transfer image receiving sheet after transfer of transfer layer) ≦ 200% (1-1) Preferably, the combination of the present disclosure satisfies the following formula (1-2). (20 degree gloss of thermal transfer image receiving sheet) - (20 degree gloss of thermal transfer image receiving sheet after transfer of transfer layer) ≦ 145% (1-2) More preferably, the combination of the present disclosure satisfies the following formula (1-3). (20 degree gloss of thermal transfer image receiving sheet) - (20 degree gloss of thermal transfer image receiving sheet after transfer of transfer layer) ≦ 100% (1-3) The 20 degree gloss of the thermal transfer image receiving sheet, i.e., the 20 degree gloss of the receiving layer of the thermal transfer image receiving sheet before the transfer layer is transferred, is preferably 400% or more, more preferably 600% or more, and even more preferably 800% or more. In one embodiment, the upper limit of the 20 degree gloss of the thermal transfer image receiving sheet is, for example, 1600%, preferably 1300%.
[0016] In the present disclosure, the 20 degree gloss is measured in accordance with JIS Z 8741 (published in 1997) using the following spectrophotometer or an equivalent device. (spectrophotometer) Konica Minolta, Inc., Rhopoint IQ-S ·Reflection angle: 20 degrees
[0017] The combination of the present disclosure preferably satisfies the following formula (2), and more preferably satisfies the following formula (2-1), which can further improve the glossiness of the produced print. DOI of the thermal transfer image receiving sheet after transferring the transfer layer is ≧47.5 (2) DOI of the thermal transfer image receiving sheet after transferring the transfer layer is ≧60 (2-1) The upper limit of the DOI is 100 in principle, but in one embodiment the upper limit of the DOI may be, for example, 95.
[0018] In this disclosure, distinctness of image (DOI) is measured according to ASTM D 5767 using the above spectrophotometer or an equivalent device.
[0019] Each layer of the thermal transfer sheet and the thermal transfer image receiving sheet will be described below.
[0020] [Thermal transfer sheet] <First base material> The first substrate can be any substrate without limitation as long as it has heat resistance to the thermal energy applied during thermal transfer and has mechanical strength and solvent resistance sufficient to support the transfer layer and the like provided on the first substrate.
[0021] The first substrate may be, for example, a film made of a resin material (hereinafter, simply referred to as a "resin film"). Examples of the resin material include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), 1,4-polycyclohexylene dimethylene terephthalate, and terephthalic acid-cyclohexane dimethanol-ethylene glycol copolymers; polyamides such as nylon 6 and nylon 6,6; polyolefins such as polyethylene (PE), polypropylene (PP), and polymethylpentene; vinyl resins such as polyvinyl chloride, polyvinyl alcohol (PVA), polyvinyl acetate, vinyl chloride-vinyl acetate copolymers, polyvinyl acetoacetal, polyvinyl butyral, and polyvinyl pyrrolidone (PVP); Examples of the resin include (meth)acrylic resins such as acrylate, polymethacrylate, polyurethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and epoxy (meth)acrylate; imide resins such as polyimide and polyetherimide; cellulose resins such as cellophane, cellulose acetate, nitrocellulose, cellulose nitrate, cellulose acetopropionate, cellulose acetate propionate (CAP), cellulose acetate hydrodiene phthalate, cellulose acetate butyrate (CAB); styrene resins such as polystyrene (PS); polycarbonate; and ionomer resins. Among the above-mentioned resin materials, polyester is preferable, PET or PEN is more preferable, and PET is particularly preferable, from the viewpoint of heat resistance and mechanical strength. In this disclosure, "(meth)acrylic" includes both "acrylic" and "methacrylic," and "(meth)acrylate" includes both "acrylate" and "methacrylate."
[0022] The above-mentioned resin film laminate can also be used as the first substrate. The resin film laminate can be produced by using a dry lamination method, a wet lamination method, an extrusion method, or the like.
[0023] When the first substrate is a resin film, the resin film may be a stretched film or an unstretched film. From the viewpoint of strength, a stretched film that is uniaxially or biaxially stretched is preferred.
[0024] The thickness of the first substrate is preferably from 2 μm to 25 μm, more preferably from 3 μm to 16 μm, which can improve the mechanical strength of the first substrate and the transfer of thermal energy during thermal transfer.
[0025] <Transfer layer> The thermal transfer sheet includes a transfer layer. In one embodiment, the transfer layer includes a release layer as a layer located closest to the first substrate. In one embodiment, the transfer layer comprises a heat seal layer on a release layer. In one embodiment, the transfer layer comprises an intermediate layer between the release layer and the heat seal layer.
[0026] (Release layer) The release layer includes a resin material and particles. Examples of resin materials include polyester, polyamide, polyolefin, vinyl resin, (meth)acrylic resin, imide resin, cellulose resin, styrene resin, polycarbonate, ionomer resin, polyurethane, silicone wax, silicone resin, silicone modified resin, fluororesin, and fluoromodified resin. Among these, from the viewpoints of the transferability of the transfer layer and the glossiness of the print to be produced, (meth)acrylic resins and styrene resins are preferred, and from the viewpoint of the durability of the transfer layer, (meth)acrylic resins are preferred. The release layer can contain one or more types of resin materials.
[0027] The glass transition temperature (Tg) of the resin material is preferably from 40° C. to 115° C., more preferably from 50° C. to 110° C., and particularly preferably from 80° C. to 108° C. This can further improve the gloss and durability of the printed matter produced. In the present disclosure, Tg is a value determined by differential scanning calorimetry (DSC) under conditions of a temperature rise rate of 3° C. / min in accordance with JIS K 7121:2012.
[0028] The weight average molecular weight (Mw) of the resin material is preferably 20,000 to 50,000, more preferably 23,000 to 48,000, and particularly preferably 24,000 to 28,000. This can further improve the gloss and durability of the printed matter produced. In the present disclosure, Mw refers to a value measured by gel permeation chromatography using polystyrene as a standard substance, and is measured in accordance with JIS-K-7252-1:2008.
[0029] The content of the resin material in the release layer is preferably from 50% by mass to 99% by mass, more preferably from 70% by mass to 98% by mass, which can further improve the transferability and durability of the transfer layer.
[0030] The release layer contains particles, which can improve the durability of the produced print. The release layer can include one or more types of particles.
[0031] The average particle size of the particles is preferably from 0.7 μm to 8 μm, more preferably from 1 μm to 6 μm, and particularly preferably from 1.3 μm to 5.5 μm, which can further improve the gloss and durability of the printed matter produced. In the present disclosure, the average particle size is a number average particle size measured using a laser diffraction particle size distribution measuring device (SALD-2000J, manufactured by Shimadzu Corporation) or an equivalent device.
[0032] The specific surface area of the particles is 2m 2 / g or more 20m 2 / g or less is preferable, and 5m 2 / g or more 20m 2 / g or less is more preferable, and 5m 2 / g or more 10m 2 This makes it possible to further improve the gloss and durability of the produced print. In the present disclosure, the specific surface area of a particle is measured in accordance with the BET method.
[0033] The particles may be inorganic particles or organic particles. Examples of inorganic particles include talc, titanium oxide, and calcium carbonate. Examples of the organic particles include particles made of resin materials such as polyester, polyamide, polyolefin, vinyl resin, (meth)acrylic resin, imide resin, cellulose resin, styrene resin, polycarbonate, and fluororesin. Polyethylene wax and the like may also be used as the organic particles.
[0034] When silica is used as the inorganic particles in the release layer, the glossiness and durability of the produced print may be insufficient, such as abrasion resistance, etc. Among the above-mentioned materials, the glossiness and abrasion resistance of the produced print can be improved by using talc.
[0035] The content of the particles relative to 100 parts by mass of the total amount of the resin material contained in the release layer is preferably from 1 to 13 parts by mass, and more preferably from 1.5 to 5 parts by mass, which can further improve the gloss and durability of the printed matter produced.
[0036] The release layer may contain an additive. Examples of the additive include a filler, a plasticizer, an antistatic agent, an ultraviolet absorbing agent, a release agent, and a dispersing agent. The release layer may contain one or more additives.
[0037] The thickness of the release layer is preferably from 0.1 μm to 5 μm, more preferably from 0.3 μm to 4 μm, and particularly preferably from 0.4 μm to 3.5 μm, which can further improve the gloss and durability of the printed matter produced.
[0038] The release layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto the first substrate or the like to form a coating film, and drying the coating film. As the coating means, for example, a known means such as a roll coating method, a reverse roll coating method, a gravure coating method, a reverse gravure coating method, a bar coating method, or a rod coating method can be used.
[0039] (Heat seal layer) In one embodiment, the transfer layer comprises a heat seal layer on a release layer. In one embodiment, the heat seal layer includes a resin material. Examples of the resin material include ultraviolet absorbing resin, (meth)acrylic resin, vinyl resin such as polyvinyl chloride and vinyl chloride-vinyl acetate copolymer, epoxy resin, polyester, polycarbonate, butyral resin, gelatin, cellulose resin, and polyamide. The heat seal layer can include one or more types of resin materials.
[0040] Among the above, ultraviolet absorbing resins are preferred. Examples of ultraviolet absorbing resins that can be used include resins obtained by reacting or bonding a reactive ultraviolet absorber with a thermoplastic resin or an ionizing radiation curable resin, and copolymers of a reactive ultraviolet absorber with a polymerizable monomer such as styrene and (meth)acrylic acid ester.
[0041] Examples of the reactive ultraviolet absorber that can be used include compounds in which an addition polymerizable double bond or a reactive group is introduced into an organic ultraviolet absorber such as a salicylate-based compound, a benzophenone-based compound, a benzotriazole-based compound, a substituted acrylonitrile-based compound, a nickel chelate-based compound, or a hindered amine-based compound.
[0042] Examples of the addition polymerizable double bond include a vinyl group, an acryloyl group, and a methacryloyl group. Examples of the reactive group include an alcoholic hydroxyl group, an amino group, a carboxyl group, an epoxy group, and an isocyanate group.
[0043] The Tg of the ultraviolet absorbing resin is preferably 70°C or more and 120°C or less, and more preferably 80°C or more and 110°C or less.
[0044] The Mw of the ultraviolet absorbing resin is preferably 15,000 or more and 50,000 or less, and more preferably 18,000 or more and 43,000 or less.
[0045] The content of the ultraviolet absorbing resin in the heat seal layer is preferably from 50% by mass to 90% by mass, and more preferably from 53% by mass to 70% by mass.
[0046] In one embodiment, the heat seal layer includes an ultraviolet absorbing material other than the ultraviolet absorbing resin. The ultraviolet absorbing material may be an inorganic material or an organic material. Examples of the inorganic material include oxides of zinc, titanium, cerium, tin, iron, etc. Examples of the organic material include benzophenone-based compounds, benzotriazole-based compounds, oxalic acid anilide-based compounds, cyanoacrylate-based compounds, and salicylate-based compounds.
[0047] In one embodiment, the heat seal layer contains one or more types of particles, which can suppress the occurrence of wrinkles in the printed matter and improve the durability and blocking resistance. The particles may be inorganic particles or organic particles. Examples of inorganic particles include silica, talc, titanium oxide, and calcium carbonate. Examples of the organic particles include particles made of resin materials such as polyester, polyamide, polyolefin, vinyl resin, (meth)acrylic resin, imide resin, cellulose resin, styrene resin, polycarbonate, and fluororesin. Polyethylene wax and the like may also be used as the organic particles. In one embodiment, among the particles, at least one selected from silica, talc, and polyethylene wax is preferable. In one embodiment, among the particles, inorganic particles are preferable, and at least one selected from silica and talc are more preferable.
[0048] The average particle size of the particles is preferably from 0.7 μm to 8 μm, more preferably from 1 μm to 6 μm, and particularly preferably from 1.3 μm to 5.5 μm, which can further improve the balance between the glossiness and wrinkle prevention properties of the produced printed matter.
[0049] The content of the particles in the heat seal layer is preferably from 0.1% by mass to 8% by mass, and more preferably from 0.1% by mass to 6% by mass.
[0050] In one embodiment, the heat seal layer contains silica, which can suppress the occurrence of wrinkles in the printed matter and can improve durability and blocking resistance.
[0051] When the average particle size of silica is A (μm) and the thickness of the heat seal layer is B (μm), the heat seal layer containing silica preferably satisfies the following formula (3), which can improve the durability of the transfer layer and the adhesion to the transfer target. 0.5B≦A≦3B (3)
[0052] The content of silica in the heat seal layer is preferably from 0.1 to 2% by mass, more preferably from 0.8 to 1.8% by mass, which can suppress wrinkling and blocking of the printed matter and improve adhesion to the image receiving paper.
[0053] In one embodiment, the heat seal layer contains talc. This can suppress the occurrence of wrinkles in the printed matter, and can improve durability and blocking resistance. The heat seal layer containing talc can reduce the gloss difference more than the heat seal layer containing silica, and therefore tends to improve the balance between the wrinkle suppression property and the glossiness of the printed matter.
[0054] When the average particle size of talc is AA (μm) and the thickness of the heat seal layer is B (μm), the heat seal layer containing talc preferably satisfies the following formula (4), which can improve the durability of the transfer layer and the adhesion to the transfer target. 0.5B≦AA≦7B (4)
[0055] The content of talc in the heat seal layer is preferably 0.1% by mass to 8% by mass, more preferably 0.1% by mass to 6% by mass, even more preferably 0.1% by mass to 2% by mass, and particularly preferably 0.8% by mass to 1.8% by mass. This can suppress the occurrence of wrinkles and blocking in the printed matter, and can also improve adhesion to the image receiving paper. The heat seal layer containing talc can further reduce the gloss difference, so the talc content can be set to be large.
[0056] In one embodiment, the heat seal layer contains polyethylene wax. This can suppress the occurrence of wrinkles in the printed matter, and can improve durability and blocking resistance. The heat seal layer containing polyethylene wax can reduce the gloss difference more than the heat seal layer containing silica, and therefore tends to improve the balance between wrinkle suppression and glossiness of the printed matter.
[0057] The number average molecular weight (Mn) of the polyethylene wax is preferably 300 or more and 10,000 or less, more preferably 400 or more and 5,000 or less, and even more preferably 400 or more and 3,000 or less. In one embodiment, from the viewpoint of further suppressing the occurrence of wrinkles in the printed matter, Mn is 800 or less. In the present disclosure, Mn means a value measured by gel permeation chromatography using polystyrene as a standard substance, and is measured in accordance with JIS-K-7252-1:2008.
[0058] The content of the polyethylene wax in the heat seal layer is preferably 0.1% by mass to 8% by mass, more preferably 0.1% by mass to 6% by mass. This can suppress the occurrence of wrinkles and blocking in the printed matter, and can also improve the adhesion to the image receiving paper. Since the heat seal layer containing the polyethylene wax can further reduce the gloss difference, the content of the polyethylene wax can be set to be large.
[0059] The heat seal layer may contain the additives described above.
[0060] The thickness of the heat seal layer is preferably from 0.1 μm to 7 μm, more preferably from 0.2 μm to 2 μm, which can further improve the gloss and durability of the printed matter produced.
[0061] The heat seal layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto a release layer or the like using the above-mentioned coating means to form a coating film, and drying the coating film.
[0062] (Middle class) In one embodiment, the transfer layer includes an intermediate layer between the release layer and the heat seal layer, which can improve adhesion between these layers.
[0063] In one embodiment, the intermediate layer includes a resin material. Examples of the resin material include polyester, vinyl resin, polyurethane, (meth)acrylic resin, polyamide, ether resin, butadiene resin such as polybutadiene and styrene-butadiene copolymer, polyol resin such as (meth)acrylic polyol, and cellulose resin. The intermediate layer can include one or more types of resin materials.
[0064] In one embodiment, the intermediate layer contains inorganic particles. Examples of inorganic particles include alumina particles, silica particles, zirconia particles, tin oxide particles, magnesium carbonate particles, magnesium hydroxide particles, and titanium oxide particles. Among these, alumina particles and silica particles are preferred. The intermediate layer can contain one or more types of inorganic particles.
[0065] The content of the inorganic particles relative to the total mass of the resin material and the inorganic particles is preferably from 5% by mass to 95% by mass, and more preferably from 20% by mass to 80% by mass. The intermediate layer may include the additive described above.
[0066] The thickness of the intermediate layer is, for example, not less than 0.2 μm and not more than 2 μm.
[0067] The intermediate layer can be formed by dispersing or dissolving the above-mentioned materials in a suitable solvent to prepare a coating liquid, applying the coating liquid onto the release layer or the like by the above-mentioned coating means to form a coating film, and drying the coating film. In one embodiment, the intermediate layer can be formed using a coating liquid containing, for example, a resin material and colloidal inorganic particles. Examples of colloidal inorganic particles include alumina sol, silica sol, zirconia sol, tin oxide sol, and titanium oxide sol.
[0068] <Back layer> In one embodiment, the thermal transfer sheet includes a back layer on the surface of the first substrate on which the transfer layer is not provided, thereby making it possible to suppress sticking, wrinkling, and the like caused by heating during thermal transfer.
[0069] In one embodiment, the back layer includes a resin material. Examples of the resin material include cellulose resin, styrene resin, vinyl resin, polyester, polyurethane, polyamide, polycarbonate, polyimide, polyamideimide, chlorinated polyolefin, silicone-modified polyurethane, fluorine-modified polyurethane, and (meth)acrylic resin. The back layer can include one or more types of resin materials.
[0070] In one embodiment, the back layer contains, as a resin material, a two-component curing resin that is cured in combination with a curing agent such as an isocyanate compound, for example, polyvinyl acetal such as polyvinyl acetoacetal and polyvinyl butyral.
[0071] In one embodiment, the back layer contains inorganic particles or organic particles, which can further suppress sticking, wrinkling, and the like caused by heating during thermal transfer.
[0072] The thickness of the back layer is preferably from 0.1 μm to 5 μm, more preferably from 0.5 μm to 2 μm, which can maintain the transferability of thermal energy during thermal transfer while suppressing sticking and wrinkling.
[0073] The back layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto the first substrate using the above-mentioned coating means to form a coating film, and drying the film.
[0074] (color material layer) In one embodiment, the thermal transfer sheet includes a colorant layer in frame sequence with the transfer layer. The color material layer includes a color material. The coloring material may be a pigment or a dye. The dye may be a sublimable dye.
[0075] Examples of coloring materials include carbon black, acetylene black, lamp black, black smoke, iron black, aniline black, silica, calcium carbonate, titanium oxide, cadmium red, cadmium phosphate red, chrome red, vermilion, red iron oxide, azo pigments, alizarin lake, quinacridone, cochineal lake perylene, yellow ocher, aureolin, cadmium yellow, cadmium orange, chrome yellow, zinc yellow, Naples yellow, nickel yellow, azo pigments, greenish yellow, ultramarine, rock ultramarine, cobalt, phthalocyanine, anthraquinone, indigo Examples of the dyes include phthalocyanine, azomethine, perylene, and aluminum pigments, as well as sublimable dyes such as diarylmethane dyes, triarylmethane dyes, thiazole dyes, merocyanine dyes, pyrazolone dyes, methine dyes, indoaniline dyes, acetophenoneazomethine dyes, pyrazoloazomethine dyes, xanthene dyes, oxazine dyes, thiazine dyes, azine dyes, acridine dyes, azo dyes, spiropyran dyes, indolinospiropyran dyes, fluoran dyes, naphthoquinone dyes, anthraquinone dyes, and quinophthalone dyes. The colorant layer may contain one or more types of colorant.
[0076] In one embodiment, the color material layer includes a resin material. Examples of the resin material include polyester, polyamide, polyolefin, vinyl resin, vinyl acetal resin, (meth)acrylic resin, cellulose resin, styrene resin, polycarbonate, phenoxy resin, and ionomer resin. The color material layer can include one or more types of resin materials.
[0077] The color material layer may contain the above-mentioned additive.
[0078] The thickness of the color material layer is, for example, 0.1 μm or more and 3 μm or less.
[0079] The colorant layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto a first substrate or the like using the above-mentioned coating means to form a coating film, and drying the coating film. When the colorant layer is a melt transfer type colorant layer, the release layer may be provided between the first substrate and the colorant layer, which can further improve the transferability of the colorant layer.
[0080] [Thermal transfer image receiving sheet] (Second base material) As the second substrate, a paper substrate or the above-mentioned resin film can be used. Paper substrates include, for example, fine paper, art paper, coated paper, resin coated paper, cast coated paper, paperboard, synthetic paper, and impregnated paper.
[0081] Additionally, a laminate of two or more paper substrates, a laminate of two or more resin films, or a laminate of a paper substrate and a resin film can be used as the second substrate.
[0082] The thickness of the second base material is, for example, not less than 30 μm and not more than 300 μm.
[0083] (glossy layer) Examples of the gloss layer include the following first to fourth embodiments. The gloss layer of the first embodiment is constituted by a laminate including a resin film and a vapor-deposited film formed on one surface of the resin film. Examples of the resin film include the resin films described above.
[0084] The vapor-deposited film can be formed from, for example, a metal such as aluminum, zinc, silicon, magnesium, calcium, potassium, tin, sodium, titanium, lead, indium, or zirconium, or an oxide thereof. The thickness of the evaporated film is, for example, 1 nm or more and 150 nm or less.
[0085] The vapor-deposited film can be formed by, for example, a physical vapor deposition method such as vacuum deposition, sputtering, or ion plating, or a chemical vapor deposition method such as plasma chemical vapor deposition, thermal chemical vapor deposition, or photochemical vapor deposition. The gloss layer of the first embodiment can be provided on the second substrate via the adhesive layer described below.
[0086] In a second embodiment, the gloss layer includes a metallic pigment and a resin material. Examples of metal pigments include particles of aluminum, nickel, chromium, brass, tin, brass, bronze, zinc, silver, platinum, gold, and oxides thereof, as well as glass subjected to metal deposition. The gloss layer may contain one or more types of metal pigments.
[0087] The content of the metal pigment in the glossy layer is preferably from 20% by mass to 80% by mass, and more preferably from 30% by mass to 75% by mass.
[0088] Examples of the resin material include polyolefins such as polyethylene, polyurethanes, polyesters, polyamides, vinyl resins, (meth)acrylic resins, epoxy resins, cellulose resins, styrene resins, polycarbonates, and ionomer resins. The gloss layer may contain one or more types of resin materials. The gloss layer may contain the additives described above.
[0089] In the second embodiment, the gloss layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto the second substrate by the above-mentioned coating means to form a coating film, and drying the coating film.
[0090] In a third embodiment, the gloss layer includes a pearl pigment and a resin material. Examples of the pearl pigment include scaly alumina pigments and mica pigments coated with metal oxides. Examples of the metal oxide include oxides of titanium, iron, zirconium, silicon, aluminum, and cerium. The gloss layer can contain one or more types of pearl pigments.
[0091] The content of the pearl pigment in the gloss layer is preferably from 20% by mass to 80% by mass, and more preferably from 30% by mass to 75% by mass.
[0092] Examples of the resin material include polyurethane, polyester, polyamide, polyolefin such as polyethylene, vinyl resin, (meth)acrylic resin, epoxy resin, cellulose resin, styrene resin, polycarbonate, and ionomer resin. The gloss layer may contain one or more types of resin materials. The gloss layer may contain the additives described above.
[0093] In the third embodiment, the gloss layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto the second substrate by the above-mentioned coating means to form a coating film, and drying the coating film.
[0094] In the fourth embodiment, the glossy layer is made of a metal foil. The metal foil may be appropriately selected from metals such as gold, silver, copper, aluminum, and zinc. The thickness of the metal foil is, for example, not less than 5 μm and not more than 50 μm.
[0095] The metal foil may be one prepared by a conventionally known method or one available commercially. The metal foil can be provided on the second substrate via an adhesive layer described below.
[0096] (Receptive layer) The receiving layer includes a resin material. Examples of the resin material include polyurethane, polyester, polyamide, polyethylene (PE), polyolefin, vinyl resin, (meth)acrylic resin, epoxy resin, imide resin, cellulose resin, styrene resin, polycarbonate, and ionomer resin. The receiving layer can include one or more types of resin materials.
[0097] In one embodiment, the receiving layer includes a release material. Examples of the release material include solid waxes, surfactants, silicone oils, and silicone resins. The receiving layer can include one or more types of release materials. Examples of waxes include polyethylene wax, polyamide wax, and Teflon (registered trademark) powder. Examples of surfactants include fluorine-based surfactants and phosphate ester-based surfactants. The silicone oil is preferably modified silicone oil. Examples of modified silicone oils include amino-modified silicone, epoxy-modified silicone, aralkyl-modified silicone, epoxy-aralkyl-modified silicone, alcohol-modified silicone, vinyl-modified silicone, and urethane-modified silicone. The receiving layer may contain the additive described above.
[0098] The thickness of the receiving layer is, for example, not less than 0.5 μm and not more than 20 μm.
[0099] The receiving layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto a glossy layer or the like using the above-mentioned coating means to form a coating film, and drying the coating film.
[0100] (Primer layer) In one embodiment, the thermal transfer image receiving sheet includes a primer layer between any layers, for example, between the glossy layer and the receiving layer or between the porous layer and the receiving layer, which can improve adhesion between these layers.
[0101] The primer layer includes a resin material. The resin material is not limited as long as it has transparency and can achieve the above 20 degree specular gloss, and examples thereof include polyester, polyurethane, polycarbonate, (meth)acrylic resin, styrene resin, vinyl resin, and cellulose resin. The primer layer can contain one or more types of resin materials. The primer layer may contain the above-mentioned additive.
[0102] The thickness of the primer layer is, for example, not less than 0.1 μm and not more than 3.0 μm.
[0103] The primer layer can be formed by dispersing or dissolving the above materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto any layer by the above-mentioned coating means to form a coating film, and drying the coating film.
[0104] (Porous layer) In one embodiment, the thermal transfer image receiving sheet includes a porous layer. In one embodiment, the porous layer is provided between the second substrate and the glossy layer. This can improve the image density formed on the receiving layer and the transferability of the transfer layer onto the receiving layer.
[0105] In one embodiment, the porous layer is composed of a porous film having microvoids therein. Examples of resin materials constituting the porous film include polyolefins such as PE and PP, vinyl resins such as polyvinyl acetate, vinyl chloride-vinyl acetate copolymer and ethylene-vinyl acetate copolymer, polyesters such as PET and PBT, styrene resins, and polyamides. Among the above, PP or PET is particularly preferred from the viewpoints of smoothness, heat insulation, and cushioning properties of the film. The porous film may contain the additives described above.
[0106] The porous film can be produced by a known method. For example, the porous film can be produced by forming a film from a mixture of the above-mentioned resin material and incompatible organic or inorganic particles. In one embodiment, the porous film can be produced by forming a film from a mixture containing a first resin material and a second resin material having a higher melting point than the first resin material. The porous film is not limited to the one produced by the above method, and a commercially available porous film may be used.
[0107] The thickness of the porous film is, for example, not less than 10 μm and not more than 100 μm.
[0108] In one embodiment, the porous layer is a hollow particle-containing layer that includes hollow particles and a binder material. The hollow particles may be organic hollow particles made of a resin material, etc., or inorganic hollow particles made of glass, etc. Organic hollow particles are preferred because of their excellent dispersibility. Examples of the resin material constituting the organic hollow particles include styrene resin, (meth)acrylic resin, phenol resin, fluororesin, polyamide, imide resin, and polycarbonate. The hollow particles may be expanded or non-expanded.
[0109] Examples of binder materials contained in the hollow particle-containing layer include polyurethane, polyester, cellulose resin, vinyl resin, (meth)acrylic resin, polyolefin, styrene resin, gelatin and its derivatives, styrene-acrylic acid ester copolymer, polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, pullulan, dextran, dextrin, polyacrylic acid and its salts, agar, κ-carrageenan, λ-carrageenan, ι-carrageenan, casein, xanthan gum, locust bean gum, alginic acid, and gum arabic. The hollow particle-containing layer may contain the above-mentioned additives.
[0110] The thickness of the hollow particle-containing layer is, for example, 10 μm or more and 100 μm or less.
[0111] The hollow particle-containing layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, applying the coating liquid onto any layer by the above-mentioned coating means to form a coating film, and drying the coating film.
[0112] (Adhesive layer) In one embodiment, the thermal transfer image receiving sheet includes an adhesive layer between any layers, for example, between the second substrate and the glossy layer, which can improve adhesion between these layers.
[0113] The adhesive layer includes a resin material, such as vinyl resins such as polyvinyl acetate, polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer, and vinyl chloride-vinyl acetate copolymer, polyolefins such as PE and PP, polyesters such as PET and PBT, polyamides, imide resins, (meth)acrylic resins such as polyacrylate, polymethacrylate, and polymethyl methacrylate, cellulose resins such as cellulose diastase, polyol resins, and polyurethanes. When the adhesive layer contains a polyol resin, it preferably contains an isocyanate compound. The adhesive layer may contain the additive described above.
[0114] The thickness of the adhesive layer is, for example, not less than 0.5 μm and not more than 10 μm.
[0115] The adhesive layer can be formed by dispersing or dissolving the above-mentioned material in a suitable solvent to prepare a coating liquid, applying the coating liquid onto any layer by the above-mentioned coating means to form a coating film, and drying the coating film. In one embodiment, the adhesive layer can be formed by melt-extruding a resin composition containing the above-mentioned material.
[0116] An embodiment of a combination of the thermal transfer sheet and the thermal transfer image receiving sheet of the present disclosure will be described below. Note that the combination of the thermal transfer sheet and the thermal transfer image receiving sheet of the present disclosure is not limited to these embodiments.
[0117] The combination of the thermal transfer sheet and the thermal transfer image receiving sheet of the present disclosure comprises: the thermal transfer sheet comprising a first substrate and a transfer layer; The following formula (1-1) is satisfied. (20 degree gloss of thermal transfer image receiving sheet) - (20 degree gloss of thermal transfer image receiving sheet after transfer of transfer layer) ≦ 200% (1-1)
[0118] In one embodiment, the combination of the thermal transfer sheet of the present disclosure and the thermal transfer image receiving sheet satisfies the following formula (2). DOI of the thermal transfer image receiving sheet after transferring the transfer layer is ≧47.5 (2)
[0119] In one embodiment, the transfer layer comprises a release layer comprising a resin material and particles. In one embodiment, the particles are talc. In one embodiment, the particles have an average particle size of 0.7 μm or more and 8 μm or less. In one embodiment, the specific surface area of the particles is 2 m 2 / g or more 20m 2 / g or less. In one embodiment, the content of the particles relative to 100 parts by mass of the total amount of the resin material contained in the release layer is 1 part by mass or more and 13 parts by mass or less. In one embodiment, the glass transition temperature of the resin material is 40°C or higher and 115°C or lower. In one embodiment, the release layer has a thickness of 0.1 μm to 5 μm.
[0120] In one embodiment, the transfer layer comprises a heat seal layer on a release layer. In one embodiment, the heat seal layer comprises an ultraviolet absorbing resin. In one embodiment, the heat seal layer comprises at least one selected from silica, talc, and polyethylene wax. EXAMPLES
[0121] The above combinations of the present disclosure will be described in more detail below with reference to examples, but the above combinations of the present disclosure are not limited to these examples. Hereinafter, for materials for which the solid content is written, the blending amount before conversion into solid content is shown.
[0122] Example 1 A coating liquid for a peeling layer having the following composition was applied to one side of a PET film having a thickness of 4.5 μm, and dried to form a peeling layer having a thickness of 1 μm. A coating liquid for an intermediate layer having the following composition was applied to the peeling layer, and dried to form an intermediate layer having a thickness of 0.5 μm. A coating liquid for a heat-sealing layer having the following composition was applied to the intermediate layer, and dried to form a heat-sealing layer having a thickness of 1 μm. In Example 1, the transfer layer is composed of a peeling layer, an intermediate layer, and a heat-sealing layer. A coating liquid for a back layer having the following composition was applied to the surface of the PET film opposite to the surface on which the transfer layer was formed, and dried to form a back layer having a thickness of 0.8 μm. In this way, a thermal transfer sheet was obtained.
[0123] <Coating solution for release layer> (Meth)acrylic resin A 100 parts by mass (Mitsubishi Chemical Corporation, Dianale (registered trademark) BR-116, Tg50℃, Mw45,000) Talc A 3 parts by weight (Microace (registered trademark) P-3, manufactured by Nippon Talc Co., Ltd. Average particle size 5μm, specific surface area 8m 2 / g) Methyl ethyl ketone (MEK) 306 parts by weight
[0124] <Coating fluid for intermediate layer> Alumina sol 30 parts by weight (Nissan Chemical Co., Ltd., Aluminasol 200, average primary particle size 10nm x 100nm, solid content 10% by mass) Polyvinylpyrrolidone 3 parts by weight (ISP, K-90) ·Water 50 parts by mass Isopropyl alcohol (IPA) 17 parts by weight
[0125] <Coating solution for heat seal layer> UV-absorbing resin: 63 parts by weight (Copolymer of monomer having ultraviolet absorbing skeleton and methyl methacrylate, molar ratio of 3:7, Tg 90°C, Mw 20,000 to 40,000, RUVA-93 manufactured by Otsuka Chemical Co., Ltd. was used as the monomer having ultraviolet absorbing skeleton) Vinyl chloride-vinyl acetate copolymer 27 parts by weight (Nissin Chemical Industry Co., Ltd., Solvine (registered trademark) CNL) Silica C 1 part by weight (Fuji Silysia Chemical Co., Ltd., Sylysia (registered trademark) 310P, Average particle size 2.7μm) UV absorber: 9 parts by weight (BASF Japan, Tinuvin (registered trademark) 928) ·MEK 240 parts by mass Normal propyl acetate 60 parts by weight
[0126] <Coating fluid for back layer> Polyvinyl butyral 2.0 parts by weight (Sekisui Chemical Co., Ltd., S-LEC (registered trademark) BX-1) Polyisocyanate 9.2 parts by weight (DIC Corporation, Burnock (registered trademark) D750) Phosphate ester surfactant 1.3 parts by weight (Manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Plysurf (registered trademark) A208N) Talc 0.3 parts by weight (Microace (registered trademark) P-3, manufactured by Nippon Talc Co., Ltd.) Toluene 43.6 parts by weight ·MEK 43.6 parts by mass
[0127] Examples 2 to 10 and Comparative Examples 1 to 3 A thermal transfer sheet was produced in the same manner as in Example 1, except that the configuration of each layer constituting the transfer layer was changed as shown in Table 1. Examples 11 to 17 A thermal transfer sheet was produced in the same manner as in Example 3, except that in the heat seal layer coating liquid for forming the heat seal layer, the type and amount of particles were changed as shown in Table 2. The relative ratios of the ultraviolet absorbing resin and the vinyl chloride-vinyl acetate copolymer were kept the same as in Example 3, but the total amount of these was changed, and the coating liquid was prepared so that the total amount of the ultraviolet absorbing resin, the vinyl chloride-vinyl acetate copolymer, the particles, and the ultraviolet absorbing material was 100 parts by mass. Details of each component in Tables 1 and 2 are as follows. (Meth)acrylic resin B: manufactured by Mitsubishi Chemical Corporation, Dianale (registered trademark) BR-113, Tg 75°C, Mw 30,000 (Meth)acrylic resin C: manufactured by Mitsubishi Chemical Corporation, Dianale (registered trademark) BR-87, Tg 105°C, Mw 25,000 Styrene resin: Toyo Styrene Co., Ltd., G100C, Tg100℃ Talc B: Nippon Talc Co., Ltd., PG-15, Average particle diameter 1.5μm, specific surface area 18m 2 / g Polyethylene wax A: Polywax (registered trademark) 400, manufactured by Toyo Adle Co., Ltd. Polyethylene wax B: Polywax (registered trademark) 600, manufactured by Toyo Adle Co., Ltd. Polyethylene wax C: Polywax (registered trademark) 1000, manufactured by Toyo Adle Co., Ltd. Polyethylene wax D: Polywax (registered trademark) 3000, manufactured by Toyo Adle Co., Ltd. Fluororesin particles: Kitamura Co., Ltd., KTL-8N, average particle size 4μm Silica A: Silica (registered trademark) 250N, manufactured by Fuji Silysia Chemical Co., Ltd. Average particle size 5.7μm Silica B: Silica (registered trademark) 380, manufactured by Fuji Silysia Chemical Co., Ltd. Average particle size 9μm Silica C: Silica (registered trademark) 310P, manufactured by Fuji Silysia Chemical Co., Ltd. Average particle size 2.7μm
[0128] <<Measurement of gloss difference>> The 20 degree specular gloss of the receiving layer of the thermal transfer image receiving sheet prepared as described below was measured using the following spectrophotometer in accordance with JIS Z 8741 (published in 1997) and was found to be 1074%. (spectrophotometer) Konica Minolta, Inc., Rhopoint IQ-S ·Reflection angle: 20 degrees
[0129] The transfer layers of the thermal transfer sheets of the Examples and Comparative Examples were transferred onto the receiving layer of the thermal transfer image-receiving sheet using the following test printer. (Test printer) Thermal head: Kyocera Corporation, KEE-57-12GAN2-STA Heating element average resistance: 3303Ω - Main scanning resolution: 300 dpi (dot per inch) Sub-scanning resolution: 300 dpi Printing voltage: 18V Line speed: 2.0msec. / line ·Printing start temperature: 35℃ Pulse Duty Ratio: 85% Printed image: Solid black image (0 / 255 image gradation)
[0130] The 20 degree specular gloss of the transfer layer transferred onto the receiving layer of the thermal transfer image receiving sheet was measured. The measurement results and the difference from the 20 degree specular gloss of the thermal transfer image receiving sheet before the transfer layer was transferred are shown in Tables 1 and 2. In addition, the thermal transfer image receiving sheet was visually observed before and after the transfer layer was transferred, and evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 1 and 2. In addition, the specular gloss at an angle of 20 degrees was measured at three locations in the center of the thermal transfer image receiving sheet (print) in a direction perpendicular to the flow direction of the thermal transfer image receiving sheet (flow direction of the print), and the average value was recorded.
[0131] (Evaluation Criteria) A: The glossiness of the thermal transfer image-receiving sheet was about the same before and after the transfer layer was transferred. B: Depending on the observation angle, the glossiness of the thermal transfer image receiving sheet after the transfer layer is transferred is different from that before the transfer layer is transferred. The gloss of the thermal transfer image-receiving sheet was inferior, but was approximately the same. C: The glossiness of the thermal transfer image receiving sheet after the transfer layer is transferred is different from the glossiness of the thermal transfer image receiving sheet before the transfer layer is transferred. The texture was inferior, but not to the extent that it would cause any problems in practical use. D: The glossiness of the thermal transfer image receiving sheet after the transfer layer is transferred is different from the glossiness of the thermal transfer image receiving sheet before the transfer layer is transferred. The feeling of a stream was far inferior.
[0132] <Preparation of Thermal Transfer Image Receiving Sheet> A porous PP film A (manufactured by Mitsui Chemicals Tocello Co., Ltd., SP-U, thickness 36 μm) and coated paper A (manufactured by Nippon Paper Industries Co., Ltd., Utrillo (registered trademark) 157, thickness 130 μm) were bonded together via a 2.5 μm thick adhesive layer to prepare a second substrate.
[0133] A coating solution for adhesive layer having the following composition was applied to the surface of the porous PP film A of the second substrate, and dried to form an adhesive layer. A PET film A (manufactured by Toyobo Co., Ltd., Metalite KY-27-CR) having a thickness of 25 μm and having a 45 nm thick aluminum vapor deposition film on one side as a glossy layer was laminated on the adhesive layer from the vapor deposition film forming side. The thickness of the adhesive layer when dried was 2.4 μm.
[0134] A primer layer coating solution having the following composition was applied to the glossy layer surface and dried to form a primer layer having a thickness of 2.5 μm. A receiving layer coating solution having the following composition was applied to the primer layer and dried to form a receiving layer having a thickness of 4 μm. In this manner, a thermal transfer image-receiving sheet was obtained. <Coating liquid for adhesive layer> Polyol resin 30 parts by weight (Takelac (registered trademark) A-969V, manufactured by Mitsui Chemicals, Inc.) Isocyanate compound 10 parts by weight (Takenate (registered trademark) A-5, manufactured by Mitsui Chemicals, Inc.) Ethyl acetate 60 parts by weight
[0135] <Coating fluid for primer layer> Urethane resin 40 parts by weight (Tosoh Corporation, Nipporan (registered trademark) 5199 (solid content 30% by mass)) ·MEK 15 parts by mass
[0136] <Coating solution for receiving layer> Vinyl chloride-vinyl acetate copolymer 60 parts by weight (Nissin Chemical Industry Co., Ltd., Solvine (registered trademark) C) Epoxy modified silicone resin 1.2 parts by weight (Shin-Etsu Chemical Co., Ltd., X-22-3000T) Methylstyryl-modified silicone resin 0.6 parts by weight (Shin-Etsu Chemical Co., Ltd., X-24-510) ·MEK 2.5 parts by mass Toluene 2.5 parts by weight
[0137] <<Image Clarity (DOI) Evaluation>> The DOI in the transfer layer transferred onto the receiving layer of the thermal transfer image receiving sheet was measured using the above spectrophotometer and evaluated according to the following evaluation criteria. The results are shown in Tables 1 and 2.
[0138] (Evaluation Criteria) A: The DOI value was 60 or higher. B: The DOI value was 47.5 or greater but less than 60. C: The DOI value was less than 47.5.
[0139] <<Abrasion resistance evaluation>> The surface of the transfer layer transferred onto the receiving layer of the thermal transfer image receiving sheet was rubbed under the following conditions using a Gakushin Tester (manufactured by Suga Test Instruments Co., Ltd.). The state of the transfer layer surface after rubbing was visually observed and evaluated based on the following evaluation criteria. The results are shown in Tables 1 and 2.
[0140] (Evaluation Criteria) A: No scratches were found on the surface. B: Some scratches were found on the surface. C: Many scratches were found on the surface. (Rubbing conditions) Friction material: Kanakin No. 3 Load capacity: 300g Number of round trips: 10 round trips
[0141] [Table 1] [Table 2]
[0142] The thermal transfer image-receiving sheet obtained in <Preparation of thermal transfer image-receiving sheet> was cut to a size of 5 mm x 30 mm. Double-sided tape was attached to the cut thermal transfer image-receiving sheet so that the tape did not protrude from the sheet, and the cut thermal transfer image-receiving sheet was attached to the double-sided tape. This process was repeated until the total thickness reached 8 mm, thereby obtaining a laminate.
[0143] The prepared laminate of 5 mm x 30 mm x 8 mm was fixed to one side of the ink ribbon flange receiving part of a printer (DS-RX1HS, manufactured by Dai Nippon Printing Co., Ltd.) with double-sided tape. A protective layer panel of a genuine ink ribbon for DS-RX1HS was cut out, and a thermal transfer sheet of the embodiment was cut and pasted on that part to prepare a test ink ribbon. This test ink ribbon was set in the above printer. Under such conditions that wrinkles are likely to occur on the printed matter, a white solid image (255 / 255 image gradation; with transfer layer transfer) was printed on the receiving layer of the thermal transfer image receiving sheet, and the presence or absence of wrinkles on the printed matter was visually confirmed.
[0144] As a result, compared to Example 10 in which no intermediate layer or heat seal layer was provided, Examples 1 to 9 in which an intermediate layer and a heat seal layer were provided had more suppressed occurrence of wrinkles in the printed matter. Compared to Example 11, in which no particles were added to the heat seal layer, Examples 3 and 12 to 15, in which silica, talc or polyethylene wax was added, showed greater suppression of wrinkles on the printed matter, with Example 3 showing particularly great suppression of wrinkles on the printed matter. Among Examples 14 to 17 in which polyethylene wax was used, the occurrence of wrinkles in the printed matter was suppressed more in Examples 14 to 15 in which the number average molecular weight of the polyethylene wax was smaller. [Explanation of symbols]
[0145] 10: Thermal transfer sheet 11: First base material 12: Transfer layer 13: Release layer 14: Heat seal layer 15: Middle class 16: Back layer 20: Thermal transfer image receiving sheet 21:Second base material 22: Glossy layer 23: Receptive layer
Claims
1. A combination of a thermal transfer sheet and a thermal transfer image receiving sheet, The thermal transfer sheet comprises a first substrate and a transfer layer, the thermal transfer image receiving sheet comprises a second substrate, a glossy layer, and a receiving layer in this order; the transfer layer comprises a release layer containing a resin material and talc; the receiving layer of the thermal transfer image receiving sheet has a 20 degree gloss of 400% or more, as measured in accordance with JIS Z 8741 (published in 1997), before the transfer layer is transferred; A combination of a thermal transfer sheet and a thermal transfer image receiving sheet that satisfies the following formula (1-1): (20 degree gloss of the thermal transfer image receiving sheet)−(20 degree gloss of the thermal transfer image receiving sheet after the transfer layer is transferred)≦200% (1−1)
2. A combination of the thermal transfer sheet according to claim 1 and a thermal transfer image receiving sheet, which satisfies the following formula (2): DOI of the thermal transfer image receiving sheet after the transfer layer is transferred is ≧47.5 (2)
3. 3. The combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to claim 1, wherein the glossy layer is constituted by a laminate comprising a resin film and a vapor deposition film formed on one surface of the resin film.
4. The combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to claim 1 or 2, wherein the glossy layer contains a metallic pigment and a resin material.
5. 5. A combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to claim 1, wherein the average particle size of the talc is from 0.7 μm to 8 μm.
6. The specific surface area of the talc is 2 m 2 / g or more 20m 2 6. A combination of the thermal transfer sheet according to claim 1 and a thermal transfer image receiving sheet, wherein the thermal transfer sheet has a viscosity of 1 / g or less.
7. A combination of a thermal transfer sheet and a thermal transfer image receiving sheet as described in any one of claims 1 to 6, wherein the content of the talc relative to a total of 100 parts by mass of the resin material contained in the release layer is 1 part by mass or more and 13 parts by mass or less.
8. 8. A combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to claim 1, wherein the glass transition temperature of the resin material is 40° C. or higher and 115° C. or lower.
9. 9. A combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to claim 1, wherein the thickness of the release layer is from 0.1 μm to 5 μm.
10. The combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to any one of claims 1 to 9, wherein the transfer layer comprises a heat seal layer on the release layer.
11. The combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to claim 10, wherein the heat seal layer comprises an ultraviolet absorbing resin.
12. 12. The combination of the thermal transfer sheet and the thermal transfer image receiving sheet according to claim 10 or 11, wherein the heat seal layer contains at least one selected from the group consisting of silica, talc and polyethylene wax.
Citation Information
Patent Citations
Sublimation transfer recording medium and method for sublimation transfer recording using it
JP2000025349A
Sublimation type thermal transfer recording sheet
JP2000118152A
Image display medium with metallic image and thermal transfer sheet
JP2003266956A
Thermal transfer sheet
JP2012101370A
Thermal transfer sheet
JP2015085688A